Beutefang des Fischadlers - Rüppell, Georg; Möller, Wilhelm (IWF (Göttingen), 1981)
Pandion haliaëtus. Beutesuche, Stoßmanöver, Start- und Hebeflugmaßnahmen Auseinandersetzungen mit der Beute, Zehenöffnen, -schließen, Steigflug, Gefiederschütteln. Mit Zeitdehnung. : Pandion haliaëtus: search flight; plunge-diving; special behaviour during and after taking off; struggles with the fish; opening and closing of the talons; climbing; shaking the plumage in the air. With slow-motion.